Evaluation of Commercial Disinfectants against Staphylococcus lentus and Micrococcus spp. of Poultry Origin. (25th September 2020) - Saha, Otun; Rakhi, Nadira Naznin; Istiaq, Arif; Islam, Israt; Sultana, Munawar; Hossain, M. Anwar; Rahaman, Md. Mizanur
Abstract : Introduction . Effective sanitation strategies for poultry farms require an appropriate selection of the disinfectant based on the contaminants present and their sensitivity to the disinfectants. Aim . The current study investigated the prevalence of streptococci/micrococci in poultry farms of Bangladesh and the efficacy of commercial disinfectants (Savlon, Lysol, Quatovet, Virkon S, and Virocid) along with alcohol against these pathogens to adopt appropriate strategies. Materials and Methods . Conventional approaches and the 16S rRNA gene sequencing were performed to confirm the isolates at the species level along with microtiter biofilm assay to determine their biofilm-forming ability. Efficacy of the disinfectants was tested against those isolates using agar well diffusion and minimum inhibitory concentration (MIC) test by broth dilution method using different dilutions of the disinfectants. Results . Staphylococcus lentus ( n  = 32), Micrococcus luteus ( n  = 7), and Micrococcus aloeverae ( n  = 4) were confirmed among 102 presumptively screened streptococci/micrococci isolates from 43 samples. No single disinfectant showed equally high efficacy against all three bacterial species in agar well diffusion test, although Virocid showed the lowest MIC against all three of them. Lysol was least effective among the commercial disinfectants by both MIC and diffusion method, although each commercial disinfectant was more effective than alcohol. Considering both the average diameter of the inhibition zones and the MIC values, efficacy can be interpreted as Virocid > Quatovet > Savlon > Virkon S > Lysol. Although the efficacy decreased with decreasing concentration, the disinfectants retained a satisfactory level of efficacy at 50% concentration. Among test pathogens, M. aloeverae was the most sensitive to the disinfectants and the weakest biofilm producers, whereas 4/14 S. lentus and 1/5 M. luteus were strong biofilm producers, which may cause more reduction in the efficacy in environmental conditions. Conclusion . As no ideal disinfectant was found in the study, the efficacy of the disinfectants should be routinely evaluated and validated to ensure the sanitation standards in the poultry sector.